Using differential reinforcement for all to manage disruptive behaviors: three class interventions at kindergarten and primary school - Pansu, Pascal; Freyssinet, Irène; Le Hénaff, Benjamin (Frontiers in Education, 2024)
Disruptive behaviors produce harmful effects, which reduce students' well-being and learning opportunities. This paper presents a new strategy named Differential Reinforcement for All (DR-All), which has been inspired by DR and Social Learning Theory. We conducted one study in which we applied DR-All to three classes with first grade students (intervention 1), then in kindergarten (intervention 2), and fifth grade students (intervention 3). In all three interventions, the measurements of student-student relationships and disruptive behaviors were taken one week before implementation and after two weeks of implementation. In intervention 1, disruptive behaviors were measured again one year after, among the 10 students who remained with the same teacher the following year. Concerning student-student relationships, we only observed one effect, which was a positive effect on the most rejected pupils in the first-grade intervention, who were significantly less rejected by their classmates after the implementation. However, the results of all three interventions showed a significant decrease in the frequency of disruptive behaviors after the strategy implementation. This was also true for the intervention 1 measurement one year later. To conclude, the consistent application of DR-All can reduce disruptive behaviors in the classroom.